1993
DOI: 10.1111/j.1432-1033.1993.tb18435.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation in cellular prostaglandin synthesis of type‐II phospholipase A2 secreted and anchored on cell‐surface heparan sulfate proteoglycan

Abstract: Rat‐liver‐derived BRL‐3A cells, which express both type‐II phospholipase A2 (PLA2) and cytosolic PLA2 (cPLA2), generated prostaglandin E2 (PGE2) in the presence of fetal calf serum. When the cells were treated with tumor necrosis factor (TNF), PGE2 generation was greatly stimulated. The production of PGE2 observed in both cases was suppressed by a type‐II PLA2‐specific inhibitor, thielocin A1. Appreciable amounts of type‐II PLA2 were released into the medium from the TNF‐stimulated cells when heparin was added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 40 publications
6
50
0
1
Order By: Relevance
“…These data agree with reports showing that arachidonic acid may increase insulin secretion via an extracellular, Ca 2C -independent pathway (Band et al, 1992). A possible interaction between PLA 2 and the cell membrane leading to phospholipid breakdown and the formation of prostaglandin and arachidonic acid has been suggested (Smith and Waite, 1992;Suga et al, 1993). The ability of arachidonic acid to increase insulin secretion appears to be a consequence of its action at several sites including a possible interaction with K C channels (Ordway et al, 1989;Juhl et al, 2003), and the stimulation of adenylyl cyclase (Engelhard et al, 1978), guanylyl cyclase (Gerzer et al, 1985), PKC (Metz, 1988), and Ca 2C -calmodulin kinase (Piomelli and Greengard, 1991).…”
Section: Discussionsupporting
confidence: 80%
“…These data agree with reports showing that arachidonic acid may increase insulin secretion via an extracellular, Ca 2C -independent pathway (Band et al, 1992). A possible interaction between PLA 2 and the cell membrane leading to phospholipid breakdown and the formation of prostaglandin and arachidonic acid has been suggested (Smith and Waite, 1992;Suga et al, 1993). The ability of arachidonic acid to increase insulin secretion appears to be a consequence of its action at several sites including a possible interaction with K C channels (Ordway et al, 1989;Juhl et al, 2003), and the stimulation of adenylyl cyclase (Engelhard et al, 1978), guanylyl cyclase (Gerzer et al, 1985), PKC (Metz, 1988), and Ca 2C -calmodulin kinase (Piomelli and Greengard, 1991).…”
Section: Discussionsupporting
confidence: 80%
“…It has been proposed that group IIa PLA 2 is tethered to cell surfaces by binding to heparan sulfate proteoglycan, and that this binding is important for the hydro-lysis of cell phospholipids. Rat liver-derived BRL-3A cells secrete group IIa PLA 2 , and appreciable amounts of this enzyme are found in the extracellular medium only when free heparin, heparan sulfate, or dextran sulfate are added to the culture medium (26), which is consistent with the observation that group IIa PLA 2 binds to these anionic polymers. Treatment of the cells with heparitinases results in a reduction of prostaglandin production, which suggests that binding of group IIa PLA 2 to cell surface proteoglycan augments arachidonic acid release (26).…”
supporting
confidence: 72%
“…Rat liver-derived BRL-3A cells secrete group IIa PLA 2 , and appreciable amounts of this enzyme are found in the extracellular medium only when free heparin, heparan sulfate, or dextran sulfate are added to the culture medium (26), which is consistent with the observation that group IIa PLA 2 binds to these anionic polymers. Treatment of the cells with heparitinases results in a reduction of prostaglandin production, which suggests that binding of group IIa PLA 2 to cell surface proteoglycan augments arachidonic acid release (26). Similar findings have been reported for prostaglandin production in human umbilical vein endothelial cells (11) and for degranulation of mast cells induced by exogenous rodent group IIa PLA 2 (27).…”
supporting
confidence: 72%
“…We have previously reported that the association of sPLA 2 - IIA with heparan sulfate proteoglycans on cell surfaces is a critical step in allowing this enzyme to mediate AA metabolism (9,18,20,57). The ability of sPLA 2 -IIA and sPLA 2 -V, but not sPLA 2 -IIC, to enhance AA release when forcibly expressed in two different cell lines (Figs.…”
Section: A23187-inducedmentioning
confidence: 99%
“…These close similarities suggest that the failure of sPLA 2 -IIC to mediate AA release was not due to abnormal enzymatic properties. The sPLA 2 inhibitor thielocin A1 and an antibody raised against rat sPLA 2 -IIA, which we had used in earlier studies (20,21,57), were quite specific for sPLA 2 -IIA (Table I) (21). LY311727, a structurally designed sPLA 2 inhibitor (55), was also fairly selective for sPLA 2 -IIA, although at higher concentrations it inhibited sPLA 2 -V as well (data not shown).…”
Section: A23187-inducedmentioning
confidence: 99%